Growth-and-risk trade-off - María Dolores Gadea; Luc Laeven; Gabriel Pérez-Quirós (European Central Bank (ECB), 2020)
We study the effects of credit over the business cycle, distinguishing between expansions and contractions. We find that there is a growth and risk trade-off in the pace of credit growth over the business cycle. While rapid credit growth tends to be followed by deeper recessions, we also find that credit growth has a positive impact on the duration of expansions. This poses a trade-off for the policymaker: Limiting the buildup of financial risk to avoid a deep recession can negatively affect the cumulation of economic growth during the expansion. We show that intermediate levels of credit growth maximize long-term growth while limiting volatility. Macroprudential policies should be used to manage this growth and risk trade-off, striking a balance between allowing expansions to last longer and avoiding deep recessions.
Keywords: C22; E32; E61; 330; cycles; macroprudential policies; credit growth; nancial crisis; GDP-at-risk